Diagnóstico da situação habitacional em 2010 e projeção da demanda demográfica por habitação em 20 anos no espaço intraurbano do Litoral Norte Paulista - Roberta Rosemback (2016)
The housing issue is essentially a demographic and spatial theme. It is a demographic theme because the life cycle of individuals and the changes in population size and age structure are linked to family formation and therefore to the necessity of new dwellings. It is also a spatial theme because a dwelling is associated with a land that has properties inherent to its location. Understanding the population dynamics and its relationship to the occupation of urban areas is a central point for urban planning and management. This thesis proposes a methodology for analysis of the housing situation at the municipal level. It is divided into two stages, the diagnosis and the prognosis. The diagnosis relies on seven theoretical analytical dimensions of adequacy that housing units are subjected to: physical fitting of the building; suitability of the building for the family; appropriateness as to legal issues; suitability as environmental safety; adequacy of infrastructure and public services; suitability of the location and accessibility; and adequacy of housing cost. The use of sample data from Census 2010 showed to be sufficient for the systematic analysis of five of the proposed dimensions (legal issues and environmental safety are not discussed). Still in the diagnosis context, inappropriate dwellings are classified into three levels: basic deficit, inadequacies, and inadequacies in severe level. In addition, the use of the weighting areas as units of analysis, allows reaching the intra-urban scale. On the prognosis stage, the future demographic demand for housing is calculated by the application of the Headship Ratio in population projections. This method was applied in the North Coast of São Paulo (São Sebastião, Caraguatatuba and Ubatuba) and proved to be consistent to help the design of housing policies. It numbers the different types of housing needs and allows the discussion of the well located housing, the urban life quality, and provides more detailed and territorialized reviews of the variety of inappropriateness that dwellings can present.